Pelaksanaan Bhuta Yadnya Puja Wali Di Pura Gunung Sekar Desa Adat Giri Emas - Ni Luh Putu Bela Murdiasih; I Made Wiradinatha Putra; Kadek Bima Seka (Pramana: Jurnal Hasil Penelitian, 2023)
Bali, the island which is nicknamed the Island of the Gods, has very strong beauty and culture and is very well preserved. In Bali there are also various kinds of religions, but the religion that is the most numerous is Hinduism which is known for its various kinds of religious ceremonies. The Mecaru Balig Ceremony of the Grand Oath at the puja guardian at Gunung Sekar Temple, Giri Emas Traditional Village, Buleleng Regency, is a ritual that belongs to the Bhuta Yadnya ceremony, this ceremony is carried out because Gunung Sekar Temple has just completed the Nganteg Linggih Manawaratna temple ceremony and the Mecaru ceremony uses various kinds of animals such as cows, chickens, dogs and also other animals. This uniqueness is what is very interesting to research and make a scientific work.